2022
DOI: 10.1371/journal.pone.0276904
|View full text |Cite
|
Sign up to set email alerts
|

Proteome expression profiling of red blood cells during the tumorigenesis of hepatocellular carcinoma

Abstract: The early diagnosis of hepatocellular carcinoma (HCC) has not been clinically elucidated, leading to an increased mortality rate in patients with HCC. HCC is a systemic disease related to disorders of blood homeostasis, and the association between red blood cells (RBCs) and HCC tumorigenesis remains elusive. We performed data-independent acquisition proteomic analyses of 72 clinical RBC samples, including HCC (n = 30), liver cirrhosis (LC, n = 17), and healthy controls (n = 25), and characterized the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Additionally, Helwa et al proposed that tumour cells may interact with RBCs, potentially through galectin-4, which although primarily expressed in gastrointestinal epithelial cells, has implications in various cancers 8 . Furthermore, we have recently observed that the presence of RBCs in CTCs short-term cultures is associated with poorer patient outcomes 14 and we have also demonstrated that the protein profiles of RBCs in cancer patients are altered compared to cancer-free donors 15,16 .…”
Section: Introductionmentioning
confidence: 85%
“…Additionally, Helwa et al proposed that tumour cells may interact with RBCs, potentially through galectin-4, which although primarily expressed in gastrointestinal epithelial cells, has implications in various cancers 8 . Furthermore, we have recently observed that the presence of RBCs in CTCs short-term cultures is associated with poorer patient outcomes 14 and we have also demonstrated that the protein profiles of RBCs in cancer patients are altered compared to cancer-free donors 15,16 .…”
Section: Introductionmentioning
confidence: 85%
“…However, Mcfadzean et al reported that patients with HCC have lower haemoglobin levels than healthy controls [13]. Wang et al revealed that decreased haemoglobin levels are associated with HCC tumourigenesis [14]. Furthermore, Boogaerts et al reported that anaemia induces tumour hypoxia, facilitates tumour-associated changes within neoplastic cells, and promotes tumour survival and malignant progression [15].…”
Section: Discussionmentioning
confidence: 99%
“…We also included a high-confidence canonical erythrocyte proteome defined by reconciling proteomic data through supervised machine learning [86]. There is increasing interest in using RBCs within the context of clinical proteomics [91] and transfusion medicine [29]; therefore, we included several studies that explore alterations in the RBC proteome due to various pathological disease states [75,80,83,85,87,88] and refrigerated storage under blood bank conditions [26,84,85], increasing the utility of RBC-GEM for biomarker discovery [43]. Because several proteomic datasets contained outdated and alternate accessions [18,19,[70][71][72][73][74]76], the unavoidable consequence of routine database updates and previous database deprecations [92], we consolidated all identifiers into a list and utilized UniProtKB mapping service to update all protein identifiers to current UniProtKB accessions, pruning obsolete and unreviewed proteins from the list.…”
Section: Proteomic Data Was Collected Across 28 Datasets To Facilitat...mentioning
confidence: 99%